Thermo mechanical analyses and characterizations of TiNiCu shape memory alloy structures developed by laser additive manufacturing. (December 2019) - Shiva, S.; Yadaiah, N.; Palani, I.A.; Paul, C.P.; Bindra, K.S.
Graphical abstract: Highlights: Thermo mechanical analyses is performed numerically and experimentally for TiNiCu developed by laser additive manufacturing. The formation of alloy was excellent without any porosity. Micro-Hardness increases with the increment of Cu percentage in the TiNiCu Alloy. Presence of phase transformation confirmed for all three samples developed. Abstract: Three different compositions of TiNiCu (Ti50Ni (50−x) Cux (x = 10, 20 and 30)) shape memory alloys (SMA) were developed using an intelligent manufacturing technique of laser additive manufacturing (LAM). Based on a numerical analysis the nature and amount of residual stress flow was predicted. By implementing finite element method (FEM) with Gaussian distributed volumetric heat source, the deposition process was simulated. The numerical and experimental analyses were at par with each other. The developed samples were subjected to several characterizations in order to determine the best among them. Scanning electron microscopy (SEM), atomic force microscopy (AFM), were used to study the surface morphology of the samples. The mechanical properties were studied using micro-hardness test and compression test. X-Ray diffraction (XRD) was deployed to investigate the crystalline nature of the samples. The phase transformation ability of the samples were determined by differential scanning calorimetry (DSC). The SEM revealed the deposition of all three samples to be homogeneous. The AFM results showed the grain size of TiNiCu10 to be 20.12 nm, the smallest among the samples. The micro-hardness and ultimate strength of TiNiCu10 was found to be 242 VHN and MPa respectively. XRD reveals the presence of three step transformation for TiNiCu20 sample. From the results, LAM process was considered as a successful methodology in developing TiNiCu bulk SMA structures. The properties of laser additive manufactured TiNiCu10 was found to be the best among the developed samples.